First records of Glyphus marsupialis Filhol, 1884 (Decapoda: Pasiphaeidae) in southwestern Atlantic deep waters and extensions of the known distribution of two Pasiphaea species - Cardoso, Irene; Martins, Déborah Elena Galvão; Cintra, Israel Hidenburgo Aniceto; Alves-Júnior, Flávio De Almeida (Zootaxa, 2024)
The Pasiphaeidae Dana, 1852 are a marine shrimp family occurring in both shallow and deeper waters, with its greatest diversity occurring in tropical and subtropical deep seas. This family includes seven genera and 104 species, and is globally distributed. Currently, the genus Pasiphaea Savigny, 1816 includes 73 species, seven of them recorded in the southwestern Atlantic. The genus Glyphus Filhol, 1884 is monotypic and is known from the Indo-Pacific region, the East Pacific Ocean and in the Eastern Atlantic. Herein, we report the first record of the genus in the southwestern Atlantic, completing a cosmopolitan distributional pattern. Further, two new records of Pasiphaea species are commented upon (P. major Hayashi, 2006; P. tarda Kroyer, 1845) along the Northern coastline of the Brazilian coast (Amapá state), also reporting a new host interaction between Thalassomyces sp. and P. major. This is the first record of this Ellobiopsidae genus in the South Atlantic Ocean. The material herein analyzed was sampled by the ReviZEE Program/North, in 1996/2001, during deep-water trawls in the Amazonian slope (Amapá state), at depths from 250 to 1100 m. All material is deposited in the Coleção Carcinológica do Laboratório de Crustáceos (Labcrus)/Universidade Federal Rural da Amazônia (UFRA). The global distribution of Glyphus is commonly observed in deep species and although it has been occasionally contested by the discovery of species complexes (using very detailed morphological and molecular data analyses) with the currently available information, the present material is clearly identifiable as G. marsupialis.